Primary Pleuropulmonary Synovial Sarcoma: A Case - Fatima Zahra Mrabet; Hafsa El Ouazzani; Leila El Akkari; Sanaa Hammi; Jamal Eddine Bourkadi; Fouad Zouaidia (Case Reports in Pulmonology)
Primary pleuropulmonary synovial sarcoma is extremely rare. The diagnosis can only be made after having eliminated an extrapleuropulmonary localization in the past and at the time of diagnosis. Our presentation is about a 40-year-old woman having a cough and dyspnea since three weeks ago; imaging had showed a left pleurisy with pleuropulmonary process. Histological study of the biopsy confirmed the diagnosis of pleuropulmonary synovial sarcoma. PET-SCAN had not identified any extrathoracic localization. This tumor is known for its aggressive nature and high risk of metastasis. Its primitive character is retained following a diagnostic procedure of exclusion. Surgical treatment remains the best therapeutic tool when it is technically feasible; otherwise the prognosis is often unfortunate. In this paper, we report a case of primary pleuropulmonary synovial sarcoma. Through this case, we present a rare disease that is often difficult to diagnose.